2008
DOI: 10.1016/j.bcp.2007.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mouse flavin-containing monooxygenase transcript levels in lung and liver, and activity of expressed isoforms

Abstract: The significance of active vs. inactive flavin-containing monooxygenase 2 (FMO2) for human drug and xenobiotic metabolism and sensitivity is unknown, but the underlying ethnic polymorphism is well documented. We used quantitative real-time PCR to measure message levels of Fmo1, Fmo2, Fmo3 and Fmo5 in lung and liver from eight strains of eight week old female mice to determine if a strain could be identified that predominately expressed Fmo2 in lung, recapitulating the human FMO expression profile and being the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…To determine the breadth of the FMO response to TCDD, in the current project we measured mRNA levels for the five most prominent FMOs in mouse liver. As recently reported by Siddens et al (2008), the most abundant hepatic mRNA under basal (untreated) conditions in adult C57BL/6J mice is FMO5. At a dose of 30 g/kg for 24 h, TCDD significantly suppressed FMO5 mRNA levels in both male ( Fig.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…To determine the breadth of the FMO response to TCDD, in the current project we measured mRNA levels for the five most prominent FMOs in mouse liver. As recently reported by Siddens et al (2008), the most abundant hepatic mRNA under basal (untreated) conditions in adult C57BL/6J mice is FMO5. At a dose of 30 g/kg for 24 h, TCDD significantly suppressed FMO5 mRNA levels in both male ( Fig.…”
Section: Resultssupporting
confidence: 71%
“…Because of a lack of specificity and high cross-reactivity with other proteins, it was not possible to distinguish FMO3 from other protein bands (data not shown). Unfortunately, suitable antibodies are currently not available for immunological characterization of mouse FMO proteins (Siddens et al, 2008). Thus, as an alternative index to the effect of TCDD on FMO protein, we measured FMO catalytic activity with methimazole, a substrate that is metabolized by multiple species of FMO , FIG.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, this is the first study to show that CYP2A5, which is one of the most abundant P450 isoforms in the mouse OM (Gu et al, 1998) and is known to be active toward a number of nasal toxicants and procarcinogens (Jalas and Hecht, 2003;Xie et al, 2010), is able to metabolize MMZ, as indicated by the decreased MMZ metabolism in Cyp2a5-null OM microsomes. Previous studies have shown that several isoforms of FMO are active in metabolizing MMZ (Siddens et al, 2008). Furthermore, NADPH-supported formation of N-methylimidazole from MMZ by rat hepatic microsomes was largely dependent on the P450 system (Lee and Neal, 1978).…”
Section: Downloaded Frommentioning
confidence: 97%
“…FMO1 is the major FMO in adult human kidney and intestine (Hines, 2006; Koukouritaki et al, 2002; Yeung et al, 2000). This pattern differs from most laboratory animals in that FMO1 is the major hepatic FMO; one exception is the mouse where there is a gender-specific expression of FMO3 in female liver (Janmohamed et al, 2004; Siddens et al, 2008). A number of mutations in FMO3 result in the heritable disease known as trimethylaminuria, in which patients have reduced capacity to N-oxygenate trimethylamine resulting in excretion of high levels of this noxious odorant in urine and sweat (Phillips and Shephard, 2008; Yeung et al, 2007; Zhang et al, 2003).…”
Section: Introductionmentioning
confidence: 69%